Dynamic and Coordinated Expression Changes of Rice Small RNAs in Response to Xanthomonas oryzae pv. oryzae - Zhao, Ying-Tao; Wang, Meng; Wang, Zhi-Min; Fang, Rong-Xiang; Wang, Xiu-Jie; Jia, Yan-Tao (Journal of genetics and genomics, 2015)
Endogenous small RNAs are newly identified players in plant immune responses, yet their roles in rice （Oryza sativa） responding to pathogens are still less understood, especially for pathogens that can cause severe yield losses. We examined the small RNA expression profiles of rice leaves at 2, 6, 12, and 24 hours post infection ofXanthomonas oryzae pv. oryzae （Xoo） virulent strain PXO99, the causal agent of rice bacterial blight disease. Dynamic expression changes of some miRNAs and trans-acting siRNAs were identified, together with a few novel miRNA targets, including an RLK gene targeted by osa-miR159a. 1. Coordinated expression changes were observed among some small RNAs in response to Xoo infection, with small RNAs exhibiting the same expression pattern tended to regulate genes in the same or related signaling pathways, including auxin and GA signaling pathways, nutrition and defense-related pathways. These findings reveal the dynamic and complex roles of small RNAs in rice-Xoo interactions, and identify new targets for regulating plant responses to Xoo.